Successful medical management of a domestic longhair cat with subdural intracranial empyema and multifocal pneumonia. Issue 2 (12th January 2017) - Cardy, Thomas J.A.; Lam, Richard; Peters, Laureen M.; McLaren, Philippa J.; Matas Riera, Màrian; De Decker, Steven
Abstract: Objective: To describe a case of successful medical management of subdural intracranial empyema and multifocal pneumonia in a domestic longhaired cat. Case Summary: A 7‐year‐and‐8‐month‐old male neutered domestic longhair cat presented with tachypnea, respiratory compromise, vestibular ataxia, obtundation, left‐sided head tilt, and multiple cranial nerve deficits. Neuroanatomical localization was multifocal with central vestibular involvement. Magnetic resonance imaging of the head indicated diffuse subdural empyema, mainly affecting the middle cranial fossa and the right cerebrum. Analysis of cerebrospinal fluid revealed degenerate neutrophils with a mixed population of intracellular bacilli. Computed tomography (CT) of the thorax was suggestive for multifocal pneumonia. Aggressive medical management with IV fluids, oxygen supplementation, mannitol boluses, dexamethasone, and broad‐spectrum antimicrobials was initiated. The cat demonstrated gradual improvement within 24 hours following initiation of treatment. General physical and neurological examinations, 9 weeks after initiating treatment, did not reveal any abnormalities. A CT examination performed at this time revealed resolution of the cat's pulmonary lesions. The cat was still free of clinical signs, 9 months after treatment was started. New or Unique Information Provided: Subdural empyema is infrequently reported in cats and has high mortality rates even following surgical treatment. To the authors' knowledge, this is the first reported case of successful medical management of a cat with subdural empyema and suggests that aggressive medical management should be attempted in cats that are not considered surgical candidates.